Effects of selected pre-treatment on the setting of cement composite from two rattan species (2009)
"The effects of aqueous extraction and removal of silified epidermis from rattan canes on the maximum hydration temperature (Tmax) and setting time (tmax) of two rattan canes species, Calamus deerratus and Lacosperma secundiflorum, mixed with portland cement were investigated. Tmax ranged from 37.0 to 58.66oC for the C.deerratus and L.secundiflorum composites respectively while tmax was from 3.7 to 26.5hrs and 7.4-25.7 hrs. Aqueous extraction increased the Tmax and reduced the tmax of the rattan-cement mixes while removal of epidermis generally caused reduction in both Tmax and tmax. The two rattan species seemed more amenable to cold than hot water extraction. Although cement extraction improved the tmax of the Calamus-cement composite more than Lacosperma cement composite. Epidermis removal, species, aquenous pre-treatment and their interactions had significant effect on the setting time than of the rattan-cement mixes. "